Potential non-invasive biomarkers of chronic sleep disorders identified by salivary metabolomic profiling among middle-aged Japanese men - Katsutaka Oishi; Yuta Yoshida; Kosuke Kaida; Kozue Terai; Hiroyuki Yamamoto; Atsushi Toyoda (Scientific Reports)
Abstract Sleep disorders have become a global social problem that increases the risk of developing mental illnesses and metabolic diseases. We aimed to identify biomarkers with which to non-invasively and objectively evaluate chronic sleep disorders. We used capillary electrophoresis–Fourier transform mass spectrometry (CE-FTMS) to analyze metabolomes in saliva collected from 50 persons each with good (≤ 2) and poor (≥ 6) sleep quality scored according to the Japanese version of the Pittsburgh Sleep Quality Index (PSQI-J) self-report questionnaire. The levels of five metabolites including glycerol and hippuric acid and eight including 2-hydroxybutyric acid (2HB), were respectively decreased and increased in participants with poor sleep quality. We established a random forest model consisting of six metabolites, including glycerol and hippuric acid, with a prediction accuracy of 0.866. Correlations between metabolites and sleep satisfaction were assessed using the Oguri-Shirakawa-Azumi sleep inventory, middle-age and aged version (OSA-MA) questionnaire. The results showed that 2’-deoxyguanosine, N1-acetylspermine, and 2,4-dihydroxybenzoic acid correlated positively, whereas glucosamine 6-phosphate and trimethylamine N-oxide correlated negatively with sleep quality. These findings suggested that changes in salivary metabolites reflect pathophysiological mechanisms of chronic sleep disorders, and that saliva samples could serve as non-invasive and objective diagnostic targets for predicting habitual sleep quality.